FRI0056 Serum IL-10 and IP-10 Levels is an Important Predictor of Response to Tocilizumab in Bio-Naïve RA Patients. (9th June 2015) - Kameda, T.; Dobashi, H.; Inoo, M.; Onishi, I.; Kurata, N.; Susaki, K.; Wakiya, R.; Ozaki, H.; Nakashima, S.; Shimada, H.; Takeuchi, Y.; Izumikawa, M.
Abstract : Background: The efficacy of biologics is different on respective RA patients. Therefore we have to select the best one among all biologics for each RA patient. On the other hand, there is few report about good predictive biomarker for the efficacy of biologics before administration 1, 2 . Consequently, it is important that we identify the novel biomarker to predict the efficacy of these agents before the administration of biologics. In our facility, we investigated the serum cytokines of responder or poor responder RA patients treated with Tocilizumab (TCZ). Thirty-three serum cytokine levels before TCZ administration were measured using MILLIPLEX MAP Human Cytokine/Chemokine®. In these serum cytokines, we extracted IL-17, IL-6, IL-10, IL-13 and IP-10 as novel biomarker to predict the effectiveness of TCZ. Objectives: We focused on serum cytokines such as IL-17, IL-6, IL-10, IL-13 and IP-10 in Bio-naïve RA patients treated with TCZ, and reveal characteristics of biomarkers to predict the efficacy of this biologics. Methods: We enrolled 27 bio-naïve RA patients before TCZ administration. We measured these five serum cytokines using ELISA. We divided these 27 bio-naïve RA patients into clinical remission (CR; DAS28 ESR <2.6) and non-CR (DAS28 ESR >2.6) group at week 24, and compared these cytokines in two groups. Results: Mean age was 57.6±15.9 years old and mean disease duration was 77.1±86.2 months. Disease activity of RA before TCZ administration was 4.48±0.87 and 5.01±1.26 with DAS28 ESR in CR (n=19) and non-CR (n=8), respectively. There was no difference in patient profile between two groups. In CR group, the serum IL-10 and IP-10 levels increased compared with non-CR group by ELISA, significantly (P<0.05). There is no difference between two groups in the levels of IL-17, IL-6 and IL-13. Conclusions: In our study, the serum levels of IL-10 and IP-10 before TCZ administration were different between CR and non-CR at week 24 with Bio-naïve RA patients. We suggest that serum IL-10 and IP-10 levels could predict the efficacy of TCZ on bio-naïve RA patients. References: Gibbons LJ, Hyrich KL. Biologic therapy for rheumatoid arthritis: clinical efficacy and predictors of response. BioDrugs. 2009; 23(2): 111-24. Chen DY, Chen YM, Chen HH, Hsieh CW, Lin CC, Lan JL. Increasing levels of circulating Th17 cells and interleukin-17 in rheumatoid arthritis patients with an inadequate response to anti-TNF-α therapy. Arthritis Res Ther. 2011 Jul 30; 13 (4): R126. Disclosure of Interest: None declared